Koszty produkcji żywca wołowego w krajach należących do międzynarodowej sieci gospodarstw porównawczych IFCN-Beef - Wilczyński, Artur (Beef Costs Production in Farms Participated in International Farm Comparison Network (IFCN-Beef), 2006)
All analyzed farms are different in terms of a production system. The majority of farms are characterized by beef breeding and the main source of return are bulls, steers and heifers. European farms sell mainly bulls for slaughtering and South American farms sell steers that influence costs and the production system. The highest cost of production is found in European countries but none of farms makes a profit from beef production. Only one farm (Argentinian) has a cost below the beef producer price.Means of production costs are carried for animal purchasing and feeding. It depends on the production system and farms specialization (animal purchasing for finishing).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 495-500